The Influence Of Consumer Behavior And Its Impact On Sales Strategies In UMKM Pastacology - Jaja, Jaja; Mulia, Septya Widi; Rachmayati, Regia Ramadhani; Gani, Toriq Abdul (Universitas Sebelas April, Fakultas Ekonomi dan Bisnis, 2026)
This study aims to examine the influence of consumer behavior on the sales strategy of the UMKM Pastacology, a local culinary business specializing in modern pasta menus at affordable prices. Consumer behavior, such as interest in product appearance, reasonable pricing, ease of digital ordering, and quality of service, plays a significant role in purchasing decisions. The research employed a qualitative descriptive method, collecting data through direct observation, interviews with management, and review of supporting documents related to marketing and product innovation. The results indicate that Pastacology adjusts its sales strategies by strengthening digital promotions, enhancing service quality, and innovating products to meet consumer needs and preferences. This study emphasizes that the success of UMKM sales strategies depends not only on product quality but also on the ability to understand and respond dynamically to consumer behavior. By implementing adaptive and consumer focused marketing strategies, Pastacology can maintain customer loyalty and remain competitive, even against celebrity-endorsed brands with high initial popularity.